Dose-dependent disruptive effects of melatonin, light and temperature on regeneration in the planarian Phagocata gracilis. Issue 2 (4th March 2019) - Beeching, Simon C.; Merritt, Brian
ABSTRACT: Many critical cellular processes, including cell proliferation and tissue repair, exhibit melatonin sensitivity. We examined the effects of exogenous melatonin, photoperiod and temperature on regeneration in Phagocata gracilis, a common North American turbellarian. Planarian regeneration involves the proliferation and migration of pluripotent stem cells capable of replacing missing body components. A characteristic mass of cells (blastema) forms during planarian regeneration, and its formation, growth and differentiation provide reliable endpoints for the study of regenerative processes. We tested the effects of exogenous melatonin at two concentrations and three photoperiods on both head and tail regenerates under seasonal diurnal temperature regimes. High temperatures and melatonin treatment increased mortality in P. gracilis, and surviving melatonin-treated subjects exhibited delayed regeneration. Asymmetrical and deficient regeneration was more common in melatonin-treated, high temperature and dark treated subjects. Additionally, high temperature and melatonin induced a novel locomotor dysfunction.